Differential expression of defense-related genes in Sinapis alba and Brassica juncea upon the infection of Alternaria brassicae - N. M. C. Nayanakantha; S. Rawat; S. Ali; A. Grover (Tropical Agricultural Research, 2016)
Alternaria black spot of rapeseed mustard caused by the necrotrophic fungal pathogen Alternaria brassicae is one of the most important plant diseases in India. A comparative study on defense gene induction was undertaken to explore the signaling mechanisms that govern the defense responses of susceptible Brassica juncea and moderately resistant Sinapis alba, belonging to the family Brassicaceae, to alternaria leaf spot disease. The expression of five selected defense-related genes viz., pathogenesis related (PR)-1, PR-2, PR-3, non-expresser of PR-1(NPR-1) and plant defensin (PDF1.2) was examined after inoculation of the seedlings of B. juncea and S. alba. Transcripts of all five defense-related genes accumulated at a greater level and earlier in S. alba than in B. juncea upon challenge inoculation with A. brassicae locally as well as systemically. Although PDF1.2 is known to be induced only by jasmonic acid (JA) and PR-1 by salicylic acid (SA) in the model plant Arabidopsis thaliana belonging to the family Brassicaceae, PDF1.2 was induced also by SA and PR-1 by JA in both B. juncea and S. alba in the present study. These results suggest that defense signaling pathways in B. juncea and S. alba are different from A. thaliana,. Although JA responsive genes are predominantly induced in most crop plants and model plants against necrotrophic fungal pathogens, both JA and SA responsive genes seem to play an important role in S. alba conferring some resistance against A. brassicae.